GOOGLE FORM APPLICATION EFFECT ON STUDENTS’ BASIC ENGLISH GRAMMAR MASTERY - Handayani, Nurma Dhona (Universitas Mahaputra Muhammad Yamin, 2023)
This research aimed to analyze the significance effect of Google Forms application toward students’ English grammar achievement and mastery. This application was used as one of the media to assess and evaluate students’ learning achievement. The design of this research was quasi-experimental research. According to the findings, the mean score of the experiment class taught by using Google Forms application was 82,5, while the mean score of the control class taught without using the Google Forms application was 68,2. Based on the mean score of both groups, it can be concluded that students in the experiment class scored higher than students in the control class, results showed that the experimental group could perform better than the control group. It has also been demonstrated that there is a significant effect on the grammar mastery of students who were taught and assessed using the Google Forms application.